SENI PEMBEBASAN : ESTETIKA SEBAGAI MEDIA PENYADARAN - Zaenuri, Ahmad; Lestari, Wahyu (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2009)
Aesthetic is not only presents beauty that give pleasure without any interest of thesense, but also gives an recognition for people in terms of developing social,economic, politic, and culture phenomenon. Aesthetic which gives beauty has essenceof recognition social and culture phenomenon changes system and culture, changesvalue system in society. Reality life is imagination, fantasy, and absurd dreams,whereas the truth and kindness of beauty only occur in ideas which create beauty of lifemanagement and the value of culture system itself. Art as a media of freedom is aneffective alternative as a means of massage delivery about situation of social life thatgrow attempts of policies of decision maker and global capitalism who create system ofculture value in society for capitalist interest.Kata Kunci : estetika, penyadaran, seni, pembebasan